THE PREVALENCE OF HYPOCALCAEMIA AMONG PATIENTS UNDERGOING THYROIDECTOMY AT A SOUTH INDIAN TERTIARY HOSPITAL: A PROSPECTIVE STUDY. - Raj, Ankit; Sah, Sujit Kumar; Kumar, Kaushalendra; Ganashree M. H; Madhu, C.P (Student's Journal of Health Research Africa, 2023)
Background After total thyroidectomy, calcium levels drop temporarily and permanently. Parathyroid glands adjacent to the thyroid glands are important for calcium metabolism. An accidental parathyroid gland injury damages calcium metabolism. Surgery-related hypocalcemia may be observed 24-48 hours later. This research also attempts to uncover the biochemical and clinical causes of hypocalcemia. This research evaluates neuromuscular stability using Chvostek and Trousseau signs. Method An observational study was conducted prospectively at JSS Hospital from Mysuru, Department of General Surgery. The patients undergoing total thyroidectomy were included in the study. the patients were thoroughly examined for their calcium levels after the surgery. Follow up were taken for 6 months if the calcium levels were less than 8 mg then it was classified as permanent hypocalcemia. The data for 100 patients was collected and then statistically analyzed for the occurrence of hypocalcemia. Results It was found that the operating time (p = 0.03), indication (p = 0.001), and level of thyroid hormone (p = 0.03) can be correlated with the occurrence of hypocalcemia. Other factors, such as gender and age of the patient, could not be correlated to the occurrence of hypocalcemia as the p-value was not statistically significant. Conclusion After total thyroidectomy, the operating time, indication, and level of thyroid hormone can be correlated with the occurrence of hypocalcemia. Checking the calcium levels after 6 hours and 24 hours of the surgery and regular follow-up can prevent the worsening of hypocalcemia. Recommendations This research highlights the importance of monitoring calcium levels following total thyroidectomy and identifies key factors, including operating time, indication, and thyroid hormone levels, that can contribute to hypocalcemia. To mitigate the risk of hypocalcemia, it is recommended to check calcium levels at specific post-operative intervals and establish a regular follow-up protocol for patients undergoing total thyroidectomy.